2022
DOI: 10.3389/fneur.2022.785670
|View full text |Cite
|
Sign up to set email alerts
|

The Attenuation Value Within the Non-hypodense Region on Non-contrast Computed Tomography of Spontaneous Cerebral Hemorrhage: A Long-Neglected Predictor of Hematoma Expansion

Abstract: Background and PurposeThe ability of attenuation value of the non-hypodense region of hematoma in non-contrast computed tomography (NCCT) for predicting hematoma expansion (HE) remains unclear. Our purpose is to explore this relationship.MethodsTwo cohorts of patients were collected for analysis. The region where we measured hematoma attenuation values was limited to the non-hypodense region that was not adjacent to the normal brain tissue on NCCT. The critical attenuation value was derived via receiver operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Concurrently, the follow-up NCCT within the initial 24 hours of admission was examined to delineate between HE and non-HE cases. Our findings confirmed that m-CTD is an independent risk factor for HE prediction (P < 0:001), corroborating previous studies [20,21]. When amalgamated with other factors, the predictive accuracy was enhanced, underscoring m-CTD's ability to independently anticipate HE occurrence and, when utilized as a contributing factor, augmenting the precision of the predictive model.…”
Section: Discussionsupporting
confidence: 90%
“…Concurrently, the follow-up NCCT within the initial 24 hours of admission was examined to delineate between HE and non-HE cases. Our findings confirmed that m-CTD is an independent risk factor for HE prediction (P < 0:001), corroborating previous studies [20,21]. When amalgamated with other factors, the predictive accuracy was enhanced, underscoring m-CTD's ability to independently anticipate HE occurrence and, when utilized as a contributing factor, augmenting the precision of the predictive model.…”
Section: Discussionsupporting
confidence: 90%